Faktor-Faktor Yang Mempengaruhi Keputusan Nasabah Memilih Pembiayaan Mudharabah Pada BPRS Gebu Prima Medan - Fachrizal Lubis; Syahrul Amsari (Universitas Islam Negeri Sumatera Utara, 2022)
This research was conducted with the aim of analyzing the factors that influence the customer's decision to choose mudharabah financing at PT. BPRS Gebu Prima Medan. The research method used in this research is quantitative research and data collection techniques in this study using a questionnaire. The data analysis used in this research is data quality test, classical assumption test, multiple linear regression test, and hypothesis testing. Based on the results of the study indicate that internal factors (X) have a positive and significant influence on mudharabah financing decisions (Y), and external factors (X) do not have a positive and significant influence on mudharabah financing decisions (Y). The results of the t-test (partial) obtained a sig value of 0.004 <0.05, therefore the provisions of the t-test (partial) can be concluded that the hypothesis Ho is rejected and Ha is accepted, which means that partially internal factors (X) affect the decision on mudharabah financing (Y).